Determination of Pipe Deformity using an Ultrasonic System - Sallehuddin Ibrahim; Nor Syahiran Zahidin; Mohd Amri Md Yunus (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Pipe deformation is of major concern as it can be an indication of pipe leakage. This paper presents an investigation using an ultrasonic system to measure the deformity on a pipe. The ultrasonic sensors are connected to aluminum probe cones which can collimate the ultrasonic signal towards the pipe surface. A deformation on the pipe will be represented by a specific voltage signal at the receiver circuit. Different weights were placed at the end of the pipe in order to make the pipe bend and thus causing deformation. Experimental result shows that the system can determine the modulus of elasticity which is identical to the predicted value. The modulus of elasticity represents the amount of deformation experienced by the pipe.